MODEL PENINGKATAN PARTISIPASI MASYARAKAT DALAM IMPLEMENTASI KEBIJAKAN KESATUAN PENGELOLAAN HUTAN : STUDI KASUS DI KPH MODEL KABUPATEN BANJAR, KALIMANTAN SELATAN - Idin Saepudin Ruhimat (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2013)
Community participation is one of the important factors that determine the effectiveness of policy implementation of Forest Management Units (FMU) in Indonesia. However, community participation in FMU policy implementation in several places are still relatively low so that inhibiting the FMU policy implementation. This study aims to analyze the influence model of ability, opportunity, and motivation to community participation and to formulate models of community participation enhancement in FMU policy implementationin Banjar Regency. The analytical method used is Structural Equation Modeling (SEM) analysis with the help of SPSS 18 and AMOS 18. Results showed (1) motivation variables directly influence the level of community participation, while capacity and the opportunity variables indirectly influence the level of community participation, and (2) model of community participation improvement is by increasing the community motivation through efforts to increase capabilities and to expand opportunities for the community toa ctively participate in FMU policy implementation in Banjar Regency.